Therapeutic significance of full lymphadenectomy in early-stage ovarian clear cell carcinoma - Yamazaki, Hiroyuki (J Gynecol Oncol, 2018)
OBJECTIVES: This study evaluated the therapeutic significance of full lymphadenectomy in early-stage ovarian clear cell carcinoma (OCCC). METHODS: We retrospectively reviewed records of 127 consecutive patients with pT1/pT2 and M0 OCCC who were treated between January 1995 and December 2015. We compared survival outcomes between those who did and did not undergo para-aortic lymph node dissection (PAND), and analyzed independent prognostic factors (Cox proportional hazards model with backward stepwise elimination). RESULTS: Of the 127 patients, 36 (28%) did not undergo lymphadenectomy; 12 (10%) patients underwent pelvic lymph node dissection (PLND) only; and 79 (62%) patients underwent both PLND and PAND. Of the 91 patients with lymphadenectomy, 11 (12%) had lymph node metastasis (LNM). The PAND(−) and PAND(+) groups did not significantly differ in age, distribution of pT status, radiologically enlarged lymph nodes, positive peritoneal cytology, capsule rupture, peritoneal involvement, and combined chemotherapy. Cox regression multivariate analysis confirmed that older age (hazard ratio [HR]=2.1; 95% confidence interval [CI]=1.0–4.3), LNM (HR=4.4; 95% CI=1.7–11.6), and positive peritoneal cytology (HR=4.2; 95% CI=2.1–8.4) were significantly and independently related to poor disease-specific survival (DSS), but implementation of both PLND and PAND (HR=0.4; 95% CI=0.2–0.8) were significantly and independently related to longer DSS. CONCLUSION: Although few in number, there are some patients with early-stage OCCC who can benefit from full lymphadenectomy. Its therapeutic role should be continuously investigated in OCCC patients at potential risk of LNM.